Assessing the level of competence in automated trading among Malaysian traders - Zarith Sofia, Zulkifli; Hairuddin, Mohammad; Miswan, Surip; Nurnadiah, Zamri; Mustafa, Mamat; Sahimel Azwal, Sulaiman (Penerbit UTHM, 2023)
In today's technology world, financial trading instrument such as stock, currencies, futures, and acts is now done electronically via the internet due to technological improvements. Financial market trading traders apply technical and fundamental analyses to forecast the best price when buying or selling the finance instrument, and they develop their trading tactics and strategies with technical analysis tools. The objective of this research is to figure out the level of competence that Malaysian retail traders have in Automated or Algorithmic Trading (AT) focusing on currency trading. The searches were conducted on a sample of Malaysian retail traders. The viewpoints of retail traders were investigated using a questionnaire designed specifically for this purpose. The data was analyzed using statistical software (SPSS). The findings of this study reveal that Malaysian traders have an excellent comprehension of AT. This study is useful for traders and researchers who want to design their own AT systems in the future.